An alternative nighttime radiative cooling paint using glass microspheres in water-based acrylic paint - Wanichart, Huttakorn; Wootthikanokkhan, Jatuphorn; Luangchaisri, Chumphon (Creative Science, 2023)
An alternative method for producing radiative cooling paint using sustainable and cost-effective green materials, which can significantly reduce indoor temperatures. Prior research on radiative cooling systems revealed that multilayer metal oxide systems require expensive raw materials and high-end facilities, limiting large-scale production. Therefore, this study aimed to identify optimal conditions for producing radiative cooling paint using commercial spherical glass microspheres and titanium dioxide nanoparticles. The study investigated the effect of glass microsphere size, quantity, and coating thickness on emissivity and light reflectance. Results showed that glass microsphere size did not significantly affect emissivity. However, increasing coating thickness and glass microsphere quantity initially increased emissivity but stabilized at saturation points. The addition of glass microspheres decreased light reflectance, increasing temperatures during the daytime. The radiative cooling efficiency of the paint was tested, and the results showed that the glass microsphere content significantly affected the reduction in daytime temperatures. A mixture content of 45 and 75 wt% reduced the temperature by 2.96 and 3.09 °C, respectively, lower than the ambient temperature during the nighttime. The double layer of titanium dioxide/glass microspheres paint was more effective at cooling than the single layer of 45% glass microspheres, despite similar emissivity values. HIGHLIGHTS Commercial spherical glass microspheres and titanium dioxide nanoparticles are used as raw materials. Glass microsphere quantity and coating thickness are found to affect emissivity and light reflectance. A mixture of 45 and 75wt% glass microsphere content is shown to significantly reduce nighttime temperatures. Double layer paint is more effective at cooling than single layer paint despite similar emissivity values. GRAPHICAL ABSTRACT